Evolution of Modern and Ancient Orogenic Belts - Rodolfo Carosi; Mario Da Costa Campos Neto; Haakon Fossen; Chiara Montomoli; Matteo Simonetti (Geosciences)
Orogens are broadly grouped into accretionary and collisional types [...]